A nickel-borate nanoarray: a highly active 3D oxygen-evolving catalyst electrode operating in near-neutral water. Issue 21 (28th February 2017) - Ji, Xuqiang; Cui, Liang; Liu, Danni; Hao, Shuai; Liu, Jingquan; Qu, Fengli; Ma, Yongjun; Du, Gu; Asiri, Abdullah M.; Sun, Xuping
Abstract : A nickel-borate nanoarray on carbon cloth (Ni-Bi/CC) derived from NiO/CC shows high activity and durability for water oxidation electrocatalysis in a borate electrolyte (pH 9.2), offering a current density of 10 mA cm −2 at an overpotential of 470 mV. Abstract : The exploration of high-performance and cost-effective water oxidation catalysts operating under mild conditions is still urgent and challenging. In this communication, a nickel-borate nanoarray supported on carbon cloth (Ni-Bi/CC) has been fabricated through oxidative polarization of a nickel oxide nanoarray on CC (NiO/CC) in a borate electrolyte (pH 9.2). As a 3D electrode, this Ni-Bi/CC exhibits superior catalytic activity for water oxidation in 0.1 M potassium borate (K-Bi) solution, yielding a geometrical catalytic current density of 10 mA cm −2 at an overpotential of 470 mV. Notably, this electrode also demonstrates outstanding long-term electrochemical durability for 25 h with 100% Faradaic efficiency.